Responsive Guest Encapsulation of Dynamic Conjugated Microporous Polymers - Xu, Lai (Sci Rep, 2016)
The host-guest complexes of conjugated microporous polymers encapsulating C(60) and dye molecules have been investigated systematically. The orientation of guest molecules inside the cavities, have different terms: inside the open cavities of the polymer, or inside the cavities formed by packing different polymers. The host backbone shows responsive dynamic behavior in order to accommodate the size and shape of incoming guest molecule or guest aggregates. Simulations show that the host-guest binding of conjugated polymers is stronger than that of non-conjugated polymers. This detailed study could provide a clear picture for the host-guest interaction for dynamic conjugated microporous polymers. The mechanism obtained could guide designing new conjugated microporous polymers.